PENGARUH LITERASI KEUANGAN, FINANCIAL TECHNOLOGY DAN PENDAMPINGAN PEMERINTAH TERHADAP PERKEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) - Nabilla Khoirun Nisa, Salma; Lindananty, Lindananty (STIA MALANG, 2024)
This research aimed to analyze the influence of financial literacy, government assistance and financial technology on the development of Small and Medium Enterprises (SMEs). This type of research is quantitative research. The respondents of this research were members of the Malang City Amangtiwi UKM Association with a total of 40 members. The data analysis method used is multiple regression. Research shows that financial literacy does not affect the development of SMEs. This showsthat financial literacy does not contribute to business development. Meanwhile, financial technology and government assistance have a positive influence on the development of SMEs. This shows that the higher the use of financial technologyand government assistance, the higher the development of SMEs.